The effects of the modified mosaic approach method on regional simulations of surface meteorological variables in western China. (2nd January 2020) - Chen, Guangyu; Wei, Zhigang; Jin, Xiaoai; Dong, Wenjie; Zhu, Xian; Liu, Yajing; Zheng, Zhiyuan; Liu, Yujia
Abstract: In this article, a modified mosaic approach method (MMAM), which considers the subgrid‐scale effect of topographical height on atmospheric forcing, is introduced. Two experiments are designed to study the effects of MMAM on surface meteorological variables in Western China within the weather research and forecasting (WRF) modelling framework during June to August 2010. Results show that MMAM has obvious effects on surface 2 m temperature improvement. Simulations of the surface 2 m temperature with MMAM are closer to the observed values over a wide range of areas, particularly around the Qinghai‐Tibet Plateau and the Tianshan Mountains. However, MMAM does not show obvious improvements on 2 m relative humidity and on 10 m wind velocity. By investigations of two selected grid cells, we find that MMAM always shows a consistent deviation (positive or negative) on 2 m temperatures compared with the control experiment throughout the study period, which is related to the fact that the difference in topographical height within the model grid does not vary with time; the differences of surface energy illustrate that MMAM directly affects the upward longwave radiation due to a revision of the forcing temperature, resulting in a redistribution of surface energy. Abstract : In the modified mosaic approach method, to consider the influence of the subgrid‐scale effect on atmospheric forcing, we get revised atmospheric forcing (fi') by using the method of vertical linear interpolation as long as we find which two levels the subgrid topographical height (hi) is between.